Case report: Unveiling genetic and phenotypic variability in Nonketotic hyperglycinemia: an atypical early onset case associated with a novel GLRX5 variant - Marin, Victor; Lebreton, Louis; Guibet, Claire; Mesli, Samir; Redonnet-Vernhet, Isabelle; Dexant, Mathurin; Lamireau, Delphine; Roche, Sandrine; Gaschignard, Margaux; Delmas, Jean; Margot, Henri; Bar, Claire (Frontiers in Genetics, 2024)
Nonketotic hyperglycinemia (NKH) is a rare, autosomal recessive metabolic disorder usually associated with mutations in genes AMT, GLDC or GCSH involved in the glycine cleavage complex. Other genes have been linked with less severe NKH, associated with deficiency of lipoate cofactor such as GLRX5, LIAS, BOLA3.We identified a new case of GLRX5-mediated NKH who presented at 2-month with severe developmental delay and seizures. The initial suspicion was raised by the MRI and then confirmed by glycine measurements in cerebrospinal fluid and blood. Genetic analysis revealed a previously undescribed homozygous variant in the GLRX5 gene (NM_016417.3:c.367G>C; p.(Asp123His)). Despite medication and supportive care, he died at the age of 4 months after a sudden neurological deterioration. It was decided to limit therapeutic interventions due to the severity of the prognosis.The case was more severe than the previous GLRX5-mediated NKH described, regarding the early age at onset and the severity. Moreover, the genetic variant was located at a potentially crucial site for glutathione binding in the GLRX5 protein. This report, thereby, expands our understanding of NKH's genetic underpinnings and phenotypic variability, highlighting the crucial role of GLRX5 and other related genes in variant NKH.